Pharmacokinetics of cabozantinib tablet and capsule formulations in healthy adults. Issue 7 (August 2016) - Nguyen, Linh; Benrimoh, Natacha; Xie, Yuli; Offman, Elliot; Lacy, Steven
Abstract : Cabozantinib capsules (COMETRIQ) are approved for the treatment of patients with progressive metastatic medullary thyroid cancer. Cabozantinib tablets are investigational drug products considered to be potentially preferred pharmaceutical dosing forms. Two phase I open-label single-dose studies in healthy individuals were carried out to characterize the plasma pharmacokinetics of cabozantinib capsule and tablet formulations: a two-way crossover bioequivalence study ( n =77) comparing the tablet formulation and the marketed capsule formulation at the approved 140 mg dose and a dose-proportionality study ( n =21 per treatment arm) evaluating the 20, 40, and 60 mg tablet strengths. In the bioequivalence study, plasma exposure [area under the plasma concentration-time curve (AUC0– t and AUC0–inf )] values were similar (<10% difference) for both formulations and the 90% confidence intervals (CIs) around the ratio of geometric least-squares means (GLSM) were within the accepted bioequivalence limits of 80–125%. However, the GLSM for C max was 19% higher for the tablet formulation and the upper 90% CI for the ratio of GLSM (131.65%) was beyond the 80–125% range. Thus, the tablet and capsule formulations failed to fulfill the bioequivalence study acceptance criteria. In the dose-proportionality study, single doses of the 20, 40, and 60 mg cabozantinib tablet strengths showed dose-proportional increases where the 95% CIs for the slopes of the ln-transformed C max, AUC0– t, and AUC0–inf values versus ln-transformed cabozantinib dose included the value of 1. These findings indicate that cabozantinib plasma exposures increased proportionally with increasing cabozantinib dose over the 20–60 mg tablet strength dose range.